THE IDEOLOGY, ROLE AND ACTIVITIES OF HEZBOLLAH IN THE CONTEXT OF MIDDLE EASTERN CONFLICTS AND INTERNATIONAL SECURITY - Bursać, Boris; ТЕРЗИЋ, Предраг Р. (The Policy of National Security, 2025)
This paper offers an in-depth examination of Hezbollah, tracing its origins, evolution, ideological foundations, organisational architecture, and operational strategies. It also evaluates its multifaceted impact on regional and international arenas. Grounded in a rigorous definition of terrorism and the defining traits of modern terrorist organisations, the study underscores Hezbollah’s significance as a paradigmatic hybrid actor simultaneously functioning as a political party, social movement, terrorist entity, and paramilitary force. In this capacity, Hezbollah occupies a pivotal position within the complex geopolitical landscape of the Middle East. The primary objective of this research is to systematically examine the key factors that contributed to the formation of Hezbollah, the dynamics of its internal organisation and structure, the ideological foundations that shape its strategic objectives, and the multidimensional aspects of its activities. The analysis encompasses a detailed overview of Hezbollah’s military operations, political participation, social and humanitarian initiatives, funding mechanisms, and the evolving global perceptions surrounding the organisation. Special attention is given to Hezbollah’s role in Middle Eastern conflicts, such as the 2006 Second Lebanon War and the Syrian civil war, along with its international operations. The research methodology is based on analysing secondary sources, including relevant academic literature, reports from international organisations, media archives, and available primary documents issued by Hezbollah. A comparative and historical approach has been applied to contextualise Hezbollah’s development within the broader political and social landscape of Lebanon, particularly in light of the civil war, the 1982 Israeli invasion, and the influence of the 1979 Iranian Revolution. This multifaceted analysis contributes to a deeper understanding of the Hezbollah phenomenon and its regional and international security implications. It offers a foundation for further inquiry into the Middle East’s complex relationships between state and non-state actors.
Keywords: Hezbollah; Middle East; Lebanon; terrorism